Management of Central Retinal Artery Occlusion: A Scientific Statement From the American Heart Association. Issue 6 (8th March 2021) - Mac Grory, Brian; Schrag, Matthew; Biousse, Valérie; Furie, Karen L.; Gerhard-Herman, Marie; Lavin, Patrick J.; Sobrin, Lucia; Tjoumakaris, Stavropoula I.; Weyand, Cornelia M.; Yaghi, Shadi; ,
Abstract : Purpose: Central retinal artery occlusion (CRAO) is a form of acute ischemic stroke that causes severe visual loss and is a harbinger of further cerebrovascular and cardiovascular events. There is a paucity of scientific information on the appropriate management of CRAO, with most strategies based on observational literature and expert opinion. In this scientific statement, we critically appraise the literature on CRAO and provide a framework within which to consider acute treatment and secondary prevention. Methods: We performed a literature review of randomized controlled clinical trials, prospective and retrospective cohort studies, case-control studies, case reports, clinical guidelines, review articles, basic science articles, and editorials concerning the management of CRAO. We assembled a panel comprising experts in the fields of vascular neurology, neuro-ophthalmology, vitreo-retinal surgery, immunology, endovascular neurosurgery, and cardiology, and document sections were divided among the writing group members. Each member received an assignment to perform a literature review, synthesize the data, and offer considerations for practice. Multiple drafts were circulated among the group until consensus was achieved. Results: Acute CRAO is a medical emergency. Systems of care should evolve to prioritize early recognition and triage of CRAO to emergency medical attention. There is considerable variability in management patterns among practitioners, institutions, and subspecialty groups. The current literature suggests that treatment with intravenous tissue plasminogen activator may be effective. Patients should undergo urgent screening and treatment of vascular risk factors. There is a need for high-quality, randomized clinical trials in this field.